The adventures of Tom Sawyer : Mark Twain. - Twain, Mark, 1835-1910 (SparkNotes (Spark Publishing))
SparkNotes Literature Guides: Making the reading experience fun! When a paper is due, and dreaded exams loom, here's the lit-crit help students need to succeed! SparkNotes Literature Guides make studying smarter, better, and faster. They provide chapter-by-chapter analysis; explanations of key themes, motifs, and symbols; a review quiz; and essay topics. Lively and accessible, SparkNotes is perfect for late-night studying and paper writing. Includes: An A+ Essay--an actual literary essay written about the Spark-ed book--to show students how a paper should be written. 16 pages devoted to writing a literary essay including: a glossary of literary terms Step-by-step tutoring on how to write a literary essay A feature on how not to plagiarize.